Membangun Pesan Sosial Dalam Film Pendek “Cerdas Melanggar” dengan Cara Bercerita pada Channel Youtube Cameo Project - Ricky Wattimena; Mariska Eunike (MediaTor (Jurnal Komunikasi), 2020)
This research will discuss about how to tell a short film called “Cerdas Melanggar”. This short film will use the Narrative Paradigm theory in which there are five basic narrative concepts such as humans are the creator of storytelling, sound judgement, sound judgement is determined by human character, rationally and story selection. This is because Youtube has a medium to create interesting content and as a place networking and storytelling as well. The researcher used Narrative Paradigm Fisher’s theory to see how the story could be trusted and enjoyed by the audience. To see how the story is told, narrative data analysis is used from Tzvetan Todorov which divides the story into three plots (beginning, middle and end) and also Miles and Huberman/s inductive data analysis which is done interactively. This study uses qualitative research methods to look at a deep phenomenon and the constructivist paradigm which is a view in which the truth of a social reality is relative. The data in this study collected using interview and documentation of the short film of Cameo Project Youtube Channel. So, the result of this research stated that the story of “Cerdas Melanggar” contains coherence and truth (fidelity).